EDGE CONTRAST ANALYSIS IN PATENGAN I NATURE RESERVE FOREST, WEST JAVA BASED ON LAND COVER CLASSIFICATION USING OBJECT BASED IMAGE ANALYSIS (OBIA) METHOD - Ridwan Firdaus, Muhammad
Patengan I Nature Reserve is a nature reserve that needs to be protected and allowed to develop naturally. However, its narrow area and many changes in land functions around the area make the flora and fauna threatened with extinction. Non-forested land cover adjacent to nature reserves such as plantations and roads can exert a large influence on the edge of the area which can change land cover patterns. This study aims to determine the edge contrast of the Patengan I Nature Reserve forest and its land cover with the area bordering the reserve. The research stages consisted of field data collection, data pre-processing, land cover classification, accuracy assessment and edge contrast analysis. The area mapping field data was collected using a drone DJI Phantom 4 Pro. The pre-processing of the data includes making mosaics using Agisoft Photoscan and image cropping. The land cover classification was carried out using the Object Based Image Analysis (OBIA) method in an area of 145.81 Ha. The results of the land cover classification are assessed for accuracy by calculating producer’s accuracy and user’s accuracy using an error matrix and assessing the overall accuracy and the Kappa Index. Edge contrast analysis is calculated with Edge Contrast (ECON_MN), which is a measurement of the difference between forest land cover and adjacent land cover. The results of the land cover classification show that the Patengan I Nature Reserve forest borders on land cover in the form of tea gardens, plantations, shrubs, open land and highways. Based on the edge contrast analysis, the forest shows an edge contrast in the Patengan I Nature Reserve forest of 67,88%. This shows that the edge contrast in the Patengan I Nature Reserve is quite high and is indicated to cause edge effects and other conservation problems.